Generation and selection of naïve Fab library for parasitic antigen: Anti‐BmSXP antibodies for lymphatic filariasis. (14th September 2017) - Omar, Noorsharmimi; Hamidon, Nurul Hamizah; Yunus, Muhammad Hafiznur; Noordin, Rahmah; Choong, Yee Siew; Lim, Theam Soon
Abstract: Phage display has been applied successfully as a tool for the generation of monoclonal antibodies (mAbs). Naive antibody libraries are unique as they are able to overcome several limitations associated with conventional mAb generation methods like the hybridoma technology. Here, we performed an in vitro selection and generation of Fab antibodies against Brugia malayi SXP protein ( Bm SXP), a recombinant antigen for the detection of lymphatic filariasis. We developed a naïve multi ethnic Fab antibody library with an estimated diversity of 2.99 × 10 9 . The antibody library was used to screen for mAbs against Bm SXP recombinant antigen. Soluble monoclonal Fab antibodies against Bm SXP were successfully isolated from the naïve library. The Fab antibodies obtained were expressed and analyzed to show its binding capability. The diversity obtained from a pool of donors from various ethnic groups allowed for a diverse antibody library to be generated. The mAbs obtained were also functional in soluble form, which makes it useful for further downstream applications. We believe that the Fab mAbs are valuable for further studies and could also contribute to improvements in the diagnosis of filariasis.